Autoimmune myocarditis is not associated with left ventricular systolic dysfunction. (14th June 2019) - Mirna, Moritz; Paar, Vera; Kraus, Theo; Sotlar, Karl; Wernly, Bernhard; Pistulli, Rudin; Hoppe, Uta C.; Lichtenauer, Michael
Abstract: Background: Experimental autoimmune myocarditis (EAM) is a common animal model for the investigation of the pathophysiology of myocarditis. Because of diverging findings from previous studies, we performed serial echocardiographic examinations throughout the course of the disease and investigated the dimensions of the murine heart and left ventricular (LV) systolic function. Materials and Methods: Experimental autoimmune myocarditis was induced in male Balb/c mice by subcutaneous injection of a fragment of the α‐myosin heavy chain (MyHC‐α 614‐629: Ac‐SLKLMATLFSTYASAD). Transthoracic echocardiography was performed on days 0, 7 and 21 in healthy animals and mice with EAM. Results: Experimental autoimmune myocarditis was associated with a reduction in LV systolic function and an increase in LV internal diameter in diastole (LVID d ) and systole (LVID s ) 7 days postimmunization. After 21 days, EAM led to a significant increase in LV‐thickness (1.3‐fold increase in LV anterior wall diameter in diastole [LVAWD d ]), but there was no difference in LV systolic function between immunized animals and healthy controls. LV‐thickness correlated well with the severity of myocarditis in the histopathological examination (LVAWD d : rs = 0.603, P  = 0.003, LV anterior wall diameter in systole (LVAWD s ): rs = 0.718, P  < 0.0001). Conclusion: Our results indicate that EAM leads to an initial dilatation of the LV that is followed by ventricular "hypertrophy." On day 21, there was no significant difference in LV systolic function between immunized animals and controls. Furthermore, the ageing of the animals had a major impact on the echocardiographic parameters; therefore, the use of healthy age‐matched controls seems warranted when echocardiography is performed in rodents.